The Association between Diet and Multiple Sclerosis - Asgharzadeh, Vahid; Seyyed Rezaei, Seyyed Amin; Poor, Behroz M.; Asgharzadeh, Mohammad; Nobari, Hossein Jalaei; Taghinejad, Zahra; Kazemi, Abdolhassan; Rashedi, Jalil (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the Central Nervous System (CNS) that affects individuals between the ages of 20 and 40 years, with a higher prevalence among women. Prevalence of this disease has increased significantly in re-cent decades in different geographical areas. There is evidence to suggest that both genetic and environmental factors play a role in the development of MS. Objective: This study aims to investigate the potential relationship between diet and MS in the Azeri population of the East Azerbaijan province of Iran. Methods: 467 MS patients and 260 non-related healthy individuals under the age of 15 com-pleted a dietary demographic questionnaire. The relationship between food consumption and MS was evaluated using the obtained data. Results: MS patients had a significantly higher consumption of fat, high-fat dairy, fast food, soybean, sausages and kielbasa, pickles, and leftover food (p-value=0.0001), while healthy in-dividuals had a higher consumption of fruit (p-value=0.0001). Consumption of Meat, sweets, and fizzy drinks was also found to be higher in MS patients (p-value<0.05). There was no sig-nificant difference in the consumption of vegetables, cakes biscuits, and spices between the two groups (p-value>0.05). Conclusion: The results suggest that fruit consumption under the age of 15 may be a protective factor against MS, while the consumption of fat, high-fat dairy, fast food, soybean, sausages and kielbasa, pickles, leftover food, meat, sweets, sauce, and fizzy drinks under the age of 15, may-be risk factors for MS.
Keywords: meat